Libertad para competir en el mercado: recursos, procesos y resultados - Iguíñiz Echeverría, Javier (2011)
Freedom to compete in the market: resources, processes, and resultsHerein we analyze three concepts of market competition. Although the different aspects of freedom can be appreciated in each one of them, they make an especial contribution to some of them. We propose that the ‘neoclassical general equilibrium’ chiefly contributes to the discussion of the outcomes of an economic activity; the ‘barriers to entry’ approach calls for a study of the resources necessary to compete; and the ‘competition as a process’ approach emphasizes the competitive activity itself. Moreover, as we move from the first onwards, enriching the meaning of competition, the possibility of losing opportunities to participate in the market becomes more evident. Entry and exit are part of the competitive process. Each concept of competition responds to theories that specify or allude to certain types and distribution of economic agents’ freedoms to manoeuvre. Throughout this study, we often quote Amartya Sen with the purpose of buildingbridges between the study of competition and the approach of ‘development as freedom.